A review of fatigue management guidelines for haul truck operators in the South African coal mining industry - Yisa, Rabson (My University, 2015)
In formulating a business model, one decision which a company faces is how to structure work in terms of shift patterns. The shift patterns affect annual operating hours and other factors linked to the profitability of operations and yet they also influence the safety of operations. A haul truck driver operating a truck at an opencast mine on a 10-hour night shift has the risk of injuring or killing himself/herself or others or damaging his truck if, due to fatigue, falls asleep whilst driving. Fatigue is a complex phenomenon and emanates from a multitude of factors including excessive physical or mental exertion and insufficient sleep. Guidelines offer a practical means of reducing the risk of fatigue-related injuries. There are many fatigue management guidelines available, prompting the research question of what constitutes a quality and effective guideline. Guidelines are textual data and hence qualitative research methods were applied on a desk study of five fatigue management guidelines selected from mining and aviation industries. The five guidelines were reviewed, for process, against the 23-item AGREE II guideline development manual and, for content, against over 50 fatigue management controls from both literature and triangulation among the guidelines themselves. The key findings were that most of the sampled guidelines did not demonstrate evidence of most of the processes required to produce a quality guideline, if one has to use the guideline development manuals as a standard of measure. In terms of content in the form of controls on how to manage fatigue, which were reviewed under five clusters, there were mixed results. The key message was that for guideline developers have to follow a rigorous developmental process so that more specific and implementable controls are selected and offered to teams that are tasked to develop site-specific fatigue management plans. Quality and effective fatigue management guidelines have a big potential of assisting businesses in the management of fatigue at the workplace, including among haul truck operators.
Keywords: Coal mines and mining -- South Africa -- Safety measures;Truck drivers -- Health and hygiene -- South Africa;Industrial hygiene -- South Africa;Fatigue.